Cloud-Native Infrastructure for K-12 Assessment Logistics: A Framework for Scalable Educational Systems - Venkatesan Kandavelu (International Journal of Computational and Experimental Science and Engineering, 2026)
The modern environment of the K-12 standardized assessment logistics requires a technological infrastructure that can coordinate the complex operations of the various school districts and ensure high compliance. The emergence of cloud-native systems and microservices-based architectures has revolutionized systems that overcome the limitations of legacy systems, which had difficulty in scaling, reliability, and cost-effectiveness during peak testing times. The shift to monolithic, on-prem infrastructure to distributed, cloud-enabled systems can be seen as a radical rethink of the educational assessment logistics, which make resource allocation elastic, scale automatically, and provide greater operational agility. Current evaluation systems combine continuous integration and deployment pipelines, streamlined data processing frameworks, and advanced security architectures to provide dependable, agreeable, and efficient operationalization. Regulatory policies, such as FERPA and COPPA, offer a high degree of protection to student data, which requires a thorough security control, auditing policy, and vendor management procedures. Complex monitoring tools and chaos engineering methodologies enhance operational resilience by giving visibility in real time of system health, early anomalies, and certified and approved fault tolerance. The paradigms, as well as optimization methodologies and security frameworks, assist the educational assessment organizations in the provision of equitable, timely, and compliant assessment services at lowered operational overheads and infrastructure expenses. Such modernization initiatives may assist the larger educational objective of providing the student with fair opportunities to show learning by providing reliable, accessible, and high-quality assessment experiences.